Analysis of the Role of Social Media as an Educational Media for Preconception Nutrition Education of the Millennial Generation in Purwakarta Regency, Indonesia - Mony, Bosyahamu (Arkus, 2024)
Social media is a popular communication medium among the millennial generation. Social media can be used as an educational medium for preconception nutrition education, especially in increasing awareness of the millennial generation regarding the importance of preconception nutrition. This research aims to analyze the role of social media as an educational medium for preconception nutrition education for the millennial generation in Purwakarta Regency, Indonesia. This research uses a qualitative research method with a phenomenological approach. Data collection was carried out through in-depth interviews with 10 millennial generation people in Purwakarta Regency. The research results show that social media plays an important role in increasing the millennial generation's awareness of the importance of preconception nutrition. Social media can be used to provide accurate and up-to-date information about preconception nutrition, and can encourage the millennial generation to be more active in adopting healthy eating patterns before pregnancy.